An analysis of cost efficiency and scale economies in Mainland China and Hong Kong commercial banks - Zhang, Qidong (2016)
This study estimates the cost efficiency and scale economies of the Mainland China and Hong Kong banking sector by employing the stochastic frontier approach. The main objective is to assess the level of cost efficiency and whether the two banking sector enjoy the economies of scale in the post-reform period from 2001 to 2014. Distinct from previous studies, a one-stage approach is used to simultaneously control for the impact of heteroscedasticity on the estimation of economies of scale as well as estimating the impact of potential factors on bank cost efficiency. On average, the estimated score of cost efficiency in Mainland China and Hong Kong is 92.57 percent compared with “best practice” banks in the selected sample, and that profitability (ROA) and capitalization (equity ratio) are significant factors determining the inefficiency. Banks with higher equity and lower capitalization tend to have higher levels of cost inefficiency. Moreover, the evidence suggests that Mainland China and Hong Kong banks on average close to constant return to scale, suggesting that the two banking sectors have operated at the optimal scale and they do not enjoy scale economies.